2020
DOI: 10.1016/j.jmii.2020.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) in Kenya: Preparedness, response and transmissibility

Abstract: The world and Kenya face a potential pandemic as the respiratory virus Coronavirus Disease 2019 (COVID-19) affects world populations. Nations have been forced to intervene and issue directions under executive orders to ensure the pandemic is contained. Kenya has reported 110 confirmed COVID-19 cases (as at 2nd April, 2020), three persons have succumbed and 2 people have fully recovered. Most of the affected people had entered/returned to Kenya from different parts of the world. Most of the people who have cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…The results of this review showed the closure of food markets, limited access to food sources, which in turn resulted in starvation with many households not being able to access or afford food. Evidence shows that the outbreak of COVID-19 can cause a considerable rise in poverty among vulnerable households, including decreased access to food [26]. This could also be attributed to a loss of income during the lockdown.…”
Section: Social Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this review showed the closure of food markets, limited access to food sources, which in turn resulted in starvation with many households not being able to access or afford food. Evidence shows that the outbreak of COVID-19 can cause a considerable rise in poverty among vulnerable households, including decreased access to food [26]. This could also be attributed to a loss of income during the lockdown.…”
Section: Social Crisismentioning
confidence: 99%
“…Subjecting African communities to lockdown at home for extended periods is impossible, as people need to access their fields or otherwise find a way to acquire food. For instance, in Ethiopia, Kenya, Nigeria, and South Africa, many have violated the lockdown measures [25][26][27] and moved through public spaces like restricted areas in towns and market places in large numbers to search for or collect their daily food, despite such moves being forbidden [28]. While lockdown is intended as a measure to reduce the outbreak of COVID-19 and prevent its transmission in the affluent world, it represents a race against death to survive among many in Africa, where life has become an "avoidanceavoidance" conflict situation; be locked in at home and die of starvation, or violate the lockdown regulations to work and collect food and die from the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Africa was expected to be at a higher risk of infection due to her densely populated communities and the communicable nature of COVID-19 Kenya, among other African nations, was prioritized for monitoring by WHO due to her close links with the disease epicenter, inadequate and insufficient capacity among other challenges ( Velavan and Meyer, 2020 ). The first case in Africa was reported in Egypt on 15th February 2020 while the first case in Kenya was reported in Nairobi on 12th March 2020 by the Ministry of Health ( Aluga, 2020 ). Kenya promptly put in place several precautionary contingency measures since February 2020 to mitigate the pandemic in its early stages.…”
Section: Introductionmentioning
confidence: 99%
“…These measures included: the use of Personal Protective Equipment (PPE) such as face masks to limit the spread of COVID-19; use of surgical gloves for the protection against surfaces or items contaminated with the virus; use of alcohol-based sanitizers for disinfecting hands or surfaces and use of soaps for handwashing ( NEMA, 2020 ; MOH, 2020a ). Additional prescribed measures included the observance of social distancing, working from home, staying at home and avoiding congregation, maintaining good respiratory hygiene while coughing and sneezing, travel restrictions, provision of hand sanitizers, and handwashing in public places by proprietors and in public transport among other measures ( Aluga, 2020 ; MOH, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Within Africa, the countries with the earliest and steepest rise in cases-South Africa and Egypt-are those that have relatively stronger travel connections to early global "hotspots" in Asia and Europe. 7 This pattern also manifests within countries, as large cities with international airports and large, dense populations have borne the early brunt of the disease. In South Africa, Cape Town experienced the strongest early surge in infections, while in Nigeria it was Lagos, and in Kenya, Nairobi (much like, for example, New York in the United States).…”
Section: Istock/wilpuntmentioning
confidence: 99%